Age-related changes in circulating immune factors reveal biomarkers of immunosenescence - Zhang, Xin; Xu, Shenjie; Ye, Lu; Yin, Jingping; Zhang, Minjie; Jin, Yifeng; Li, Jie (Frontiers in Medicine, 2026)
BackgroundImmunosenescence, characterized by the decline and restructuring of immune system components with age, affects both innate and adaptive immunity. The predictive value of soluble factors in immunosenescence remains unclear.ObjectiveTo investigate the predictive value of sCD28 (Soluble CD28), sCD40L (CD40 Ligand), sCD25 (Soluble CD25), IL-6 (Interleukin-6) and sPD-1 (Soluble Programmed Cell Death Protein 1) for immunosenescence in a general population, to evaluate their diagnostic potential using ROC curve analysis, including both individual and combined detection efficacy.MethodsWe analyzed 131 healthy individuals across four age groups: young (≤44 years, n = 34), middle-aged (45–60 years, n = 31), young-old (61–70 years, n = 38), and older (>70 years, n = 28). Serum levels of sCD28, sCD40L, sCD25, IL-6, and sPD-1 were measured using ELISA. Baseline characteristics and correlations were analyzed using SPSS 25.0. ROC analysis was performed to assess diagnostic potential, with a focus on both individual markers and the combined detection of sPD-1, IL-6, and sCD28.ResultssPD-1, IL-6, and sCD28 levels positively correlated with age (p < 0.05). IL-6 had the highest individual AUC (0.77, 95%CI: 0.69–0.85; sensitivity 71%, specificity 78% at 1.22 pg./mL). Combined detection of sPD-1, IL-6, and sCD28 improved diagnostic performance, with an AUC of 0.82 (95%CI: 0.76–0.90), sensitivity of 70%, and specificity of 80% at a cut-off of 0.43.ConclusionsPD-1, IL-6, and sCD28 are associated with immunosenescence and have diagnostic potential, with IL-6 showing the highest individual efficacy. Importantly, their combined detection enhances diagnostic accuracy for immunosenescence, highlighting their synergistic predictive value for immune aging.